QRIS as a Compensation and Work Ability Moderator: Impact on Employee Performance - Riatmaja, Dodi Setiawan; Sukmaningrum, Dinda; Wibawanto, Sigit (LP3M Universitas Putra Bangsa, 2024)
This research explores the relationship between compensation, work ability, and E-Retribution QRIS technology on employee performance, with a sample of 100 employees from PT Kolektif Visi Utama Yogyakarta. Through Structural Equation Modeling (SEM) analysis using SmartPLS, it was found that compensation does not significantly influence employee performance, while work ability and the use of E-Retribution QRIS technology have a positive and significant effect on performance. The implication is that companies need to focus on developing employees' work abilities and integrating information technology to improve their performance.